Full disclosure [compact disc, unabridged] - Henderson, Dee (Brilliance Audio, 2012)
Ann Silver is a cop's cop. As the Midwest Homicide Investigator, she is called in to help local law enforcement on the worst of cases, looking for answers to murder. Hers is one of the region's most trusted investigative positions. Paul Falcon is the FBI's top murder cop in the Midwest. If the victim carried a federal badge or had a security clearance, odds are good Paul and his team see the case file or work the murder. Their lives intersect when Ann arrives to pass a case off her desk and onto his. Paul isn't expecting to meet someone, the kind that goes on the personal side of the ledger, but Ann Silver has his attention. Paul wonders just what secrets Ann is keeping, until she shows him the John Doe Killer case file, and he starts to realize just who this lady he is falling in love with really is.